Optimized utilization studies of dredging sediment for making water treatment ceramsite based on an extreme vertex design. (December 2020) - Wang, Liangkai; Shao, Yalu; Zhao, Zilong; Chen, Shuang; Shao, Xiaohou
Abstract: The minimal recycling and large accumulation of dredging sediment has resulted in a range of social and environmental problems. To solve the residual sediment disposal problems, a series of experiments utilizing the dredging sediment as ceramsite components were performed. Zeolite and bentonite were introduced as additives. In this work, the extreme vertices design method was used to determine the optimal proportion of a three-component mixture for sintering sediment ceramsite. The results showed that the maximum specific surface area of 51.68 m 2 /g and the largest porosity of 53.93% could be achieved with the optimal contents of 40.30 wt.% sediment, 39.42 wt.% zeolite, and 20.28 wt.% bentonite. The characterizations (mineralogical characteristics, physical characteristics, microstructure characteristics, and toxic metal leaching characteristics) of the sediment ceramsite were measured. The property tests of the sediment ceramsite showed that the dredging sediment played an important role in the sintering process of the ceramsite. The heating process can be divided into three stages, and the main new crystalline phases of the sediment ceramsite were clinoptilolite (Na(AlSi5 O12 )·4H2 O), albite-calcian ordered (NaCaAl(SiAl)2 O8 ) and quartz (SiO2 ). The sediment ceramsite presented a rough surface and had an abundant porous structure with elongated and interconnected pores (diameters between 0.05 and 10 μm). Additionally, the sediment ceramsite was verified to meet the standard of lightweight ceramsite (bulk density was 0.89 g/cm 3 ) and was macroporous (the mean pore size was 3.3472 μm), nontoxic (concentrations of toxic metal leaching were all below the industry standard) and suitable for the water treatment system.